2012
DOI: 10.1021/ef201325u
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the Closed-Loop Combustion Control Methodology in Modern Automotive Diesel Engines for Low-End Torque Increment Burning Biodiesel

Abstract: The interaction among biodiesel, engine calibration, and turbocharger system was investigated in a modern automotive diesel engine. In consideration of the poorer maximum torque curve derived from the use of fatty acid methyl ester (FAME) biodiesels, pure or in blends, with respect to the conventional diesel one, an experimental activity was dedicated to the investigation of the capability of the closed-loop combustion control (CLCC) technology to mitigate or improve the impact of FAME characteristics on the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…However, lowcost pressure transducers incorporated into conventional glow plugs have recently become available and are being successfully used in production diesel vehicles. [17][18][19][20][21] Previous research by the authors has shown that closed-loop diesel combustion control strategies using cylinder pressure-based feedback have the potential to enable operation within the narrow operating pathways of these advanced combustion modes for achieving low emissions of NOx and soot while maintaining stable engine operation. 13,22 To stabilize and improve the engine performance during the advanced combustion modes, the combustion phasing needs to be anchored within a narrow crank angle (CA) window close to the top dead center (TDC).…”
Section: Introductionmentioning
confidence: 99%
“…However, lowcost pressure transducers incorporated into conventional glow plugs have recently become available and are being successfully used in production diesel vehicles. [17][18][19][20][21] Previous research by the authors has shown that closed-loop diesel combustion control strategies using cylinder pressure-based feedback have the potential to enable operation within the narrow operating pathways of these advanced combustion modes for achieving low emissions of NOx and soot while maintaining stable engine operation. 13,22 To stabilize and improve the engine performance during the advanced combustion modes, the combustion phasing needs to be anchored within a narrow crank angle (CA) window close to the top dead center (TDC).…”
Section: Introductionmentioning
confidence: 99%